DINAMIKA BUDAYA PEWAYANGAN KE ARAH DUNIA REALITA DALAM WAYANG PESISIRAN - Nurhayati, Endang; Mulyana, Mulyana; Mulyani, Siti; Hardiyanto, Hardiyanto; Hartanto, Doni Dwi (Diksi, 2021)
(Title: The Dynamics of Puppet Culture Towards The World of Reality in Wayang Pesisiran). The world of puppetry is so attached to Javanese society where the changes of the times does not detract from the existence of puppets in Javanese people's lives. This study aims to describe the characteristics of coastal puppets and the dynamics of puppet culture towards the world of reality in coastal puppets using qualitative approaches. The data source used is a video of coastal puppets and interviews to Ki Kartono. Data is collected by means of listen, record, and interview. The data analysis used was the qualitative analysis of Miles &Huberman (1992). Based on the results of research, coastal puppet shows always begin by introducing the mission of the show and introducing the main characters in the play to be told. The cultural dynamics of puppetry towards the world of reality in coastal puppets contain at least six dynamics, namely: a) religious; b) greetings; c) the territory of the country; d) socio-cultural; e) the growth of life (kasampurnaning dumadi); and f) employment. The dynamics that occur in the world of puppetry indicates the dynamic in Javanese puppetry in an effort to continue to maintain its existence in modern times today. Keywords: cultural dynamics, the world of reality, wayang pesisiran